2003
DOI: 10.1067/mva.2003.94
|View full text |Cite
|
Sign up to set email alerts
|

Brachial artery dilatation after arteriovenous fistulae in patients after renal transplantation: A 10-year follow-up with ultrasound scan

Abstract: According to our results, dilatation of the brachial artery after AV is time dependent. Higher flow in the AF seems to be the main trigger of dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 10 publications
(9 reference statements)
2
64
0
3
Order By: Relevance
“…This technique not only shows the blood filling the cavity but also the jet flow passing through the arterial defect. [9,10] The color Doppler USG performed on our patients helped us in the diagnosis and determination of the surgical approach criteria. Most authors have reported that color Doppler USG is sufficient enough, even in late-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique not only shows the blood filling the cavity but also the jet flow passing through the arterial defect. [9,10] The color Doppler USG performed on our patients helped us in the diagnosis and determination of the surgical approach criteria. Most authors have reported that color Doppler USG is sufficient enough, even in late-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors have reported that color Doppler USG is sufficient enough, even in late-term follow-up. [9] The patients in our study were evaluated with color Doppler USG in the postoperative sixth month, and it was observed that all AVFs were in good condition.…”
Section: Discussionmentioning
confidence: 99%
“…Although the arterial diameter increases in all inflow arteries, distal brachial arterial segment is the most affected due to the turbulences of the proximal bifurcation [5]. The incidence of inflow arterial aneurysms is higher in patients receiving immunosuppressive therapy and corticosteroids for renal transplantation [7]. In our study, six patients who were operated for AVF aneurysms had inflow arterial aneurysms of whom four underwent renal transplantation.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, in a 10-year follow-up of clinical studies comprised of 53 patients, Janicki et al [33] determined that five (9.4%) developed an aneurysm. In addition, Eugster et al, [34] followed 38 patients for 10 years, measuring their brachial artery diameters, and found an average increase of 1 cm at the end of this period. In addition, two of the patients (5.3%) developed an aneurysm.…”
Section: Discussionmentioning
confidence: 99%